Beyond Face-Saving: Politeness Strategies in Steve Harvey’s Adult–Child Communication on Little Big Shots - Karmelia Putri; Aziez, Shinta (EUFONI: Journal of Language, Literary, and Cultural Studies, 2026)
Respectful communication plays a crucial role in children’s cognitive, emotional, and social development. Although Brown and Levinson’s politeness theory has been widely applied across various communicative contexts, previous studies have primarily examined interactions among adults and have largely focused on classifying politeness strategies rather than explaining their role in facilitating supportive communication with children. This study addresses this gap by investigating the politeness strategies employed by Steve Harvey in his interactions with child guests in the television talk show Little Big Shots. Specifically, the study examines the types of politeness strategies used and the factors influencing their selection within an adult–child communication context. Employing a qualitative content analysis design, the study analyzed seven purposively selected episodes featuring children aged three to six years with diverse talents. The data consisted of 57 dialogue exchanges, yielding 137 instances of politeness strategies because individual utterances could realize multiple strategies simultaneously. Data were analyzed using Brown and Levinson’s (1987) politeness framework following qualitative coding and thematic interpretation procedures. The findings reveal that all four politeness strategies were employed, with positive politeness emerging as the dominant strategy (56.2%), followed by bald on-record (24.1%), negative politeness (13.9%), and off-record (5.8%). Strategy selection was primarily influenced by payoff, relative power, and social distance. More importantly, the findings demonstrate that positive politeness functions not merely to mitigate face-threatening acts but also to encourage children’s participation, strengthen self-confidence, reduce interpersonal distance, and create an emotionally supportive interactional environment. By integrating Brown and Levinson’s politeness theory with Piaget’s cognitive development theory and child-centered communication principles, this study extends the application of politeness theory to intergenerational communication. The findings contribute to developmental pragmatics by demonstrating that politeness strategies serve broader interactional functions, including emotional scaffolding and communicative support, while also offering practical insights for parents, educators, caregivers, and media practitioners seeking to foster respectful communication with children.